Best practice strategies to safeguard drug prescribing and drug administration: an anthology of expert views and opinions - Seidling, Hanna; Stützle, Marion; Hoppe-Tichy, Torsten; Störzinger, Dominic; Taylor, Lenka A.; Haefeli, Walter E. (International journal of clinical pharmacy, 2016)
Background While evidence on implementation of medication safety strategies is increasing, reasons for selecting and relinquishing distinct strategies and details on implementation are typically not shared in published literature. Objective We aimed to collect and structure expert information resulting from implementing medication safety strategies to provide advice for decision-makers. Setting Medication safety experts with clinical expertise from thirteen hospitals throughout twelve European and North American countries shared their experience in workshop meetings, on-site-visits and remote structured interviews. Methods We performed an expert-based, in-depth assessment of implementation of best-practice strategies to improve drug prescribing and drug administration. Main outcome measures Workflow, variability and recommended medication safety strategies in drug prescribing and drug administration processes. Results According to the experts, institutions chose strategies that targeted process steps known to be particularly error-prone in the respective setting. Often, the selection was channeled by local constraints such as the e-health equipment and critically modulated by national context factors. In our study, the experts favored electronic prescribing with clinical decision support and medication reconciliation as most promising interventions. They agreed that self-assessment and introduction of medication safety boards were crucial to satisfy the setting-specific differences and foster successful implementation. Conclusion While general evidence for implementation of strategies to improve medication safety exists, successful selection and adaptation of a distinct strategy requires a thorough knowledge of the institute-specific constraints and an ongoing monitoring and adjustment of the implemented measures.